Pengaruh Pembelajaran Matematika Berbasis Deep Learning untuk Menikatkan Minat Belajar Siswa Kelas V Di SDN Inpres Sanolo - Kurniati; Mariamah; Abd Haris; Suciyati; Nanang Diana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning interest is one of the important factors that influence students' success in the learning process, particularly in mathematics. However, in reality, students' interest in mathematics is still relatively low because many students perceive mathematics as a difficult and boring subject. This condition causes students to be less active and less enthusiastic in participating in learning activities. This study aimed to determine the effect of Deep Learning-based mathematics instruction on the learning interest of fifth-grade students at SDN Inpres Sanolo. The study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 15 students selected using the total sampling technique, in which all members of the population are included as research participants. Since the study involved only 15 fifth-grade students, all students were used as the sample. Data were collected through observation, questionnaires, and documentation. The data were analyzed using the Paired Sample t-Test. The results showed that the implementation of Deep Learning-based mathematics instruction was able to improve students' learning interest. The average learning interest score increased from 48.3 in the pretest to 81.3 in the posttest. The results of the Paired Sample t-Test indicated a significance value of less than 0.001, meaning that there was a significant effect of Deep Learning-based mathematics instruction on students' learning interest. Furthermore, the N-Gain analysis result of 75% indicated a moderately effective category. Therefore, it can be concluded that Deep Learning-based mathematics instruction has a positive and significant effect on improving the learning interest of fifth-grade students at SDN Inpres Sanolo.